ANALISIS PENGGUNAAN BENDERA DAN LAMBANG ACEH DALAM PELAKSANAAN OTONOMI KHUSUS DI ACEH MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2006 TENTANG PEMERINTAHAN ACEH - Fakrizal, Dedek; Marzuki, Marzuki; Mustamam, Mustamam (LPPM YPITI, 2021)
The central government deemed Qanun Number 3 of 2013 concerning the flag and symbol of the region to be in conflict with the provisions of Article 6 PP. No. 77/2007 concerning Regional Symbols, also contradicts the provisions of Article 250 paragraph (1) of Law Number 23 of 2014 concerning Regional Government. The use of the Aceh flag in the framework of implementing special autonomy in Aceh is a symbol of society that shows the identity of the people and regions of Aceh, and is not a symbol of sovereignty in accordance with Article 246 of the Government Law. Judging from the aspect of its implementation, until now the provisions of the Qanun have not been implemented, even though it has been ratified by the Aceh government together with the DPRA. Thus, the Qanun on the Aceh Flag has not received legal certainty in its totality, because there are still conflicting legal substance norms contained therein.